Soil bacterial and fungal diversity and composition respond differently to desertified system restoration - Chengchen Pan; Feng Yuan; Yaling Liu; Xiaoya Yu; Jiliang Liu (PLoS ONE, 2025)
Desertification is a major ecological issue worldwide that results in the destruction of terrestrial ecosystems. Restoration of desertified ecosystems has been carried out in recent decades, but the role of soil microorganisms in this process is poorly understood. Thus, to deconstruct the effects of desertified system restoration on soil microbial communities, we examined the changes in soil characteristics as well as the variations in and drivers of soil microbial diversity and community composition of the Hulun Buir Sandy Land in Northeast China, where restoration activities have been performed for approximately 30 years. The results revealed that with desertified system restoration, plant species richness and aboveground biomass increased significantly. The soil properties, characterized by organic carbon, total nitrogen and available nitrogen content improved. Moreover, soil pH decreased significantly from 7.75 in mobile dunes to 7.17 in fixed dunes (P < 0.05). Compared to mobile dunes, the Chao1 and Shannon diversity indices of bacteria increased significantly in fixed dunes. In contrast, the fungal richness index (Chao1 index) decreased significantly during desertified system restoration. The fungal Shannon diversity index also showed a decreasing trend, although it was not significant (P > 0.05). Proteobacteria was the most prevalent bacterial phylum, with a relative abundance of over 40%. In fixed dunes, the relative abundances of Actinobacteria, Acidobacteria, Gemmatimonadetes, and Chloroflexi significantly increased, whereas the relative abundance of Firmicutes significantly decreased. For fungi, Ascomycota was the dominant phylum, with a relative abundance of 97.6% in fixed dunes compared with 82.4% in mobile dunes. Plant species richness and soil pH were the major determinants of the soil microbial communities. This research provides important insights into the changes in soil microbial communities and their relationships with environmental factors during desertified system restoration, which can help guide sustainable land management practices and the restoration of desertified areas.